Principal Approaches to Understanding Occupation and Occupational Science Found in the Chilean Journal of Occupational Therapy (2001–2012) - Rodolfo Morrison; Silvia Gómez; Enrique Henny; María Jesús Tapia; Laura Rueda (Occupational Therapy International)
Background. The progression of occupational science in Chile is documented in the main scientific publication of the field, the Chilean Journal of Occupational Therapy (RChTO). Objective. Identify approaches to understanding and applying occupation and occupational science as elucidated in the RChTO. Methodology. A systematic qualitative review of the journal (2001–2012) identified articles elucidating an approach to understanding and application operationally defined as references to specific authors, theories, models/paradigms, definitions, and other fields that support approaches to O/OS. Results. The study identified two main approaches. The first considers occupation/occupational science from a practical perspective or as a means to explain human behavior; the second considers occupation/occupational science as an object of study. Each approach is further divided into categories. Conclusion. This study provides a novel perspective on regional use of occupational science concepts. These findings contribute to our understanding of this science in context and to recognition of the cultural relevance of these scientific concepts.